Pengaruh Operating Leverage dan Struktur Modal terhadap Kinerja Keuangan pada Perusahaan Go Publik Sektor Property Dan Real Estate - Suhesti Ningsih; Wikan Budi Utami (Jurnal Akuntansi dan Pajak, 2020)
The company's financial performance is a benchmark for the success of managers in running a company. This study aims to determine the effect of operating leverage and capital structure partially or simultaneously on financial performance in the Go Public Company Property and Real Estate Sector. The sampling technique in this study is to use purposive sampling. Data analysis method in this study uses multiple regression analysis which is used to determine the effect of independent variables on the dependent variable together (F test) and partially (t test) and R2 test (coefficient of determination) carried out to find out how much influence the operating variable leverage (DOL) and capital structure (DER) on financial performance variables (ROA). From the t test results it is known that the variable operating leverage (DOL) and capital structure variables (DER) with a significance value of 0.044 and 0.015